1995
DOI: 10.1097/00000542-199511000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Midazolam on Intracellular Calcium sup 2+ and Tension in Airway Smooth Muscles

Abstract: Midazolam directly relaxes airway smooth muscles by decreasing [Ca2+]i; this can be attributed to the inhibition of the influx of extracellular Ca2+. Midazolam has no effect on the release of stored Ca2+. In addition, midazolam has no effect on Ca2+ sensitivity of the contractile apparatus. Finally, benzodiazepine antagonists, flumazenil and PK11195, have no effect on this mechanism of direct action of midazolam on airway smooth muscles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…During the 1 h post‐fura‐PE3 loading equilibration period, the strips were stimulated with 40 m M K + PSS at 5 – 10 min intervals, and the muscle length was increased in a stepwise manner after each stimulation until the developed tension reached a maximum. When exposed to 40 m M K + PSS, most strips produced a stable tension within 15 min, with or without an initial transient force response ( Kai et al ., 1993 ; 1996 ; Yoshimura et al ., 1995 ). Any strips showing instability in tension, as induced by 40 m M K + PSS, were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%
“…During the 1 h post‐fura‐PE3 loading equilibration period, the strips were stimulated with 40 m M K + PSS at 5 – 10 min intervals, and the muscle length was increased in a stepwise manner after each stimulation until the developed tension reached a maximum. When exposed to 40 m M K + PSS, most strips produced a stable tension within 15 min, with or without an initial transient force response ( Kai et al ., 1993 ; 1996 ; Yoshimura et al ., 1995 ). Any strips showing instability in tension, as induced by 40 m M K + PSS, were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%
“…However, the mechanism by which midazolam exerts bronchodilating effects has not been clearly defined. It has been reported that GABA inhibits postganglionic cholinergic neurotransmission is and, thus, the spasmolytic effect might be due to GABA receptor activation by midazolam bound to benzodiazepine 4 found that midazolam relaxed K § and carbachol-induced contraction of airway smooth muscle in accordance with a decrease in intracellular calcium by inhibition of the influx of extracellular Ca 2+, and that central and peripheral benzodiazepine antagonist could not reverse the relaxation. Therefore, voltage sensitive Ca 2 § channels may be involved in the mechanism.…”
Section: Discussionmentioning
confidence: 96%
“…However, in vivo its effect has not been studied. [2][3][4] Airway calibre is normally assessed indirectly by measuring airway resistance or compliance, which can be strongly influenced by airway secretions. 5 However, there are several reports of the relative insensitivity of indirect measurements of airway calibre.…”
mentioning
confidence: 99%
“…13,14 In astrocytes, however, there is evidence that the opposite is true. 15 Furthermore, because an increase in intracellular Ca 2+ is often responsible for the neurotoxicity associated with receptor activation, we assessed the impact of midazolam on intracellular Ca 2+ in DRG neurons.…”
Section: Midazolam-induced Increase In Intracellular Ca 2+mentioning
confidence: 99%